HUBUNGAN ANTARA PENGETAHUAN MIKROBIOLOGI DENGAN SIKAP HIGIENIS MAHASISWA PENDIDIKAN BIOLOGI ANGKATAN 2013 FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - Hasmiati Hasmiati; st Syamsudduha; Jamilah Jamilah (Jurnal Biotek, 2016)
This study aims to: (1) determine microbiological knowledge of students of Biology Education Force 2013 Faculty of MT and Teaching UIN Alauddin Makassar (2) know the attitude of hygienic education students Biology Force 2013 Faculty of MT and Teaching UIN Alauddin Makassar (3) examine the relationship between knowledge of microbiology with hygienic attitudes students Force 2013 Faculty of Biology Education and Teaching Tarbiyah UIN Alauddin Makassar.This study is a correlational study using a quantitative approach. This study used a population of 118 people drawn from all students of the Faculty of Biology Education and Teaching Tarbiyah UIN Alauddin Makassar class of 2013. Sampling was conducted using simple random sampling technique as much as 40 samples. When the study in March 2016. Data collection techniques used were a test to find out how knowledge of microbiology students Force 2013 Faculty of Biology Education and Teaching Tarbiyah UIN Alauddin Makassar and questionnaires to find out how hygienic attitudes education students Force 2013 Biology Faculty of MT and Teaching UIN Alauddin Makassar.The results showed: (1) knowledge of microbiology students of the Faculty of Biology Education and Teaching Tarbiyah UIN Alauddin Makassar class of 2013 were in the high category with an average score of 77. (2) hygienic attitudes of students of Biology Education and Teaching Faculty Tarbiyah UIN Alauddin Makassar force in p2013 were in both categories with an average score of 94. (3) there is a relationship between knowledge of microbiology with student hygienic attitude force in 2013 Faculty of Biology Education and Teaching Tarbiyah UIN Alauddin Makassar with a contribution of 24.1% to the level of siginifikansi a = 0.05 (5 %) where rhitung (0.491)> rtabel (0.263).